A Review of Nutritional Requirements of Adults Aged ≥65 Years in the UK. Issue 9 (8th June 2020) - Dorrington, Nicole; Fallaize, Rosalind; Hobbs, Ditte A; Weech, Michelle; Lovegrove, Julie A
ABSTRACT: Appropriate dietary choices in later life may reduce the risk of chronic diseases and rate of functional decline, however, there is little well-evidenced age-specific nutritional guidance in the UK for older adults, making it challenging to provide nutritional advice. Therefore, the aim of this critical review was to propose evidence-based nutritional recommendations for older adults (aged ≥65 y). Nutrients with important physiological functions in older adults were selected for inclusion in the recommendations. For these nutrients: 1 ) recommendations from the UK Scientific Advisory Committee for Nutrition (SACN) reports were reviewed and guidance retained if recent and age-specific, and 2 ) a literature search conducted where SACN guidance was not sufficient to set or confirm recommendations for older adults, searching Web of Science up to March 2020. Data extracted from a total of 190 selected publications provided evidence to support age-specific UK recommendations for protein (1.2 g·kg −1 ·d −1 ), calcium (1000 mg·d −1 ), folate (400 μg·d −1 ), vitamin B-12 (2.4 μg·d −1 ), and fluid (1.6 L·d −1 women, 2.0 L·d −1 men) for those ≥65 y. UK recommendations for carbohydrates, free sugars, dietary fiber, dietary fat and fatty acids, sodium, and alcohol for the general population are likely appropriate for older adults. Insufficient evidence was identified to confirm or change recommendations for all other selected nutrients. In general, significant gaps in current nutritional research among older adults existed, which should be addressed to support delivery of tailored nutritional guidance to this age group to promote healthy aging.